2007
DOI: 10.1007/s11199-007-9379-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thin Ideal Media Images on Women’s Self-Objectification, Mood, and Body Image

Abstract: Objectification theory (Fredrickson and Roberts, Psychology of Women Quarterly, 21, 173-206, 1997) contends that experiences of sexual objectification socialize women to engage in self-objectification. The present study used an experimental design to examine the effects of media images on self-objectification. A total of 90 Australian undergraduate women aged 18 to 35 were randomly allocated to view magazine advertisements featuring a thin woman, advertisements featuring a thin woman with at least one attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
181
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(203 citation statements)
references
References 30 publications
13
181
3
6
Order By: Relevance
“…In addition to its impact on body dissatisfaction, exposure to thin-ideal media (e.g., magazines) also leads to more negative mood (Harper & Tiggemann, 2008;Tiggemann & McGill, 2004). Similarly, one study found that spending 20 minutes on Facebook lead to more negative mood than did browsing the Internet in general (not including social networking sites) or spending no time online (Sagioglou & Greitemeyer, 2014).…”
Section: Impact Of Media Exposurementioning
confidence: 99%
“…In addition to its impact on body dissatisfaction, exposure to thin-ideal media (e.g., magazines) also leads to more negative mood (Harper & Tiggemann, 2008;Tiggemann & McGill, 2004). Similarly, one study found that spending 20 minutes on Facebook lead to more negative mood than did browsing the Internet in general (not including social networking sites) or spending no time online (Sagioglou & Greitemeyer, 2014).…”
Section: Impact Of Media Exposurementioning
confidence: 99%
“…For instance, exposure to objectifying media is likely to heighten women's self-objectification, appearance anxiety, negative mood, and body dissatisfaction (Harper & Tiggemann, 2008) and exposure to sexualized female models leads women to describe themselves in terms of appearancerelated traits (Aubrey, 2006;Aubrey, Henson, Hopper, & Smith, 2009).…”
Section: Trait Self-objectification and Attitudes Toward Harassmentmentioning
confidence: 99%
“…No es de extrañar, por tanto, que se haya encontrado un vínculo significativo entre la recepción mediática de determinados programas o la participación en determinados foros de Internet y enfermedades como la bulimia o la anorexia (Botta, 1999;Harrison y Cantor, 1997;Harrison, 2000;Harper y Tiggemann, 2008;Park, 2005;Tiggemann, 2006). Al mismo tiempo, muchas prácticas que comienzan a ser habituales -como la liposucción, la cirugía estética y otras operaciones quirúrgicas-son fruto de las imposiciones sociales vehiculadas por la publicidad y por los medios de comunicación masiva.…”
Section: Cuerpo Y Medios De Comunicaciónunclassified